TNF-α, IL-1B and IL-6 affect the differentiation ability of dental pulp stem cells - SAZAK ÖVEÇOĞLU, HESNA; AKKOÇ, TUNÇ (My University, 2023)
Background: This in vitro study examined the effect of the inflammatory cytokines (tumour necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6) on osteogenic, chondrogenic, and adipogenic differentiation of dental pulp stem cells (DPSCs) which have significant relevance in future regenerative therapies. Methods: DPSCs were isolated from the impacted third molar dental pulp and determined with flow cytometry analysis. DPSCs were divided into into 5 main groups with 3 subdivisions for each group making a total of 15 groups. Experimental groups were stimulated with TNF-α, IL-1β, IL-6, and a combination of all three to undergo osteogenic, chondrogenic, and adipogenic differentiation protocols. Next, the differentiation of each group was examined with different staining procedures under a light microscope. Histological analysis of osteogenic, chondrogenic, and adipogenic differentiated pellets was assessed using a modified Bern score. Statistical significance determined using one-way analysis of variance, and correlations were assessed using Pearson’s test (two-tailed). Results: Stimulation with inflammatory cytokines significantly inhibited the osteogenic, chondrogenic and adipogenic differentiation of DPSCs in terms of matrix and cell formation resulting in weak staining than the unstimulated groups with inflammatory cytokines. On contrary, the unstimulated groups of MSCs have shown to be highly proliferative ability in terms of osteogenic, chondrogenic, and adipogenic differentiation. Conclusions: DPSCs have high osteogenic, chondrogenic, and adipogenic differentiation capabilities. Pretreatment with inflammatory cytokines decreases the differentiation ability in vitro, thus inhibiting tissue formation.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Dental pulp stem cells; Inflammatory cytokines; Interleukin-1β; Interleukin-6; Osteogenic differentiation; Tumor necrosis factor-α